Seismic response mitigation of building structures with a novel vibro-impact dual-mass damper. (15th July 2020) - Wang, Jingjing; Wang, Bin; Liu, Zhibin; Li, Haobo; Zhang, Chao
Highlights: A vibro-impact dual-mass damper (VIDM) is proposed as a passive seismic control strategy. VIDM displays strong robustness against both frequency and energy changes. Vibro impacts in VIDM do not cause adverse effect of large structural accelerations. VIDM is affordable and applicable with small demands of reaction force and stroke. Abstract: This paper presents a comprehensive study on seismic response mitigation of building structures enabled by a novel vibro-impact dual-mass damper (VIDM). VIDMs consist of a linear oscillator and a nonlinear oscillator with impact surfaces between these two oscillators. The working principle of VIDMs is first presented via the equations of motion and the impact model of the device-attached system. The experimental studies of VIDM are subsequently carried out on a three-story steel frame structure with different column layouts. Test results show that the VIDM can exhibit strong robustness against structural frequency change and does not cause the adverse effect of excessively large structural acceleration as conventional vibro-impact-type devices do. Based on the validated numerical model, additional comparative studies under impulsive and seismic excitations are performed. Compared with tuned mass damper and cubic nonlinear energy sink, dual-mass damper and VIDM both show energy robustness and frequency robustness but the latter is preferred with a much smaller stroke demand. Therefore, the VIDM demonstrates great potential as an effective control strategy for seismic response mitigation of building structures.